Microbial iron reduction enhances in-situ control of biogenic hydrogen sulfide by FeOOH granules in sediments of polluted urban waters. (15th March 2020) - Sun, Jianliang; Wei, Li; Yin, Ran; Jiang, Feng; Shang, Chii
Abstract: This paper discusses the abiotic and biotic processes in the in-situ control of biogenic hydrogen sulfide generated from microbial sulfate reduction by ferric (Fe III ) (hydr)oxides (FeOOH) granules in the sediments of polluted urban waters. Granular ferric hydroxide (GFH, β-FeOOH) and granular ferric oxide (GFO, α-FeOOH) dosed in the organic- and sulfate-rich sediments had 180% and 19% higher sulfide removal capacities than those used for the purely abiotic removal of dissolved sulfide, respectively. The enhancement was attributable to the involvement of the biotic pathways, besides the abiotic pathways (mainly sulfide oxidation). The FeOOH granules stimulated the microbial reduction of surface Fe III by iron-reducing bacteria ( e.g., Desulfovibrio and Carnobacterium ), and increased the microbial sulfate reduction by 24%–30% under an organic-rich condition, likely due to the enhanced organic fermentation. The microbial iron reduction significantly enhanced the removal of the formed biogenic hydrogen sulfide through increasing sulfide precipitation because it remarkably promoted the release of Fe 2+ ions from the granule surface, likely due to the involvement of siderophores as ligands. This biotic pathway led to the formation of amorphous FeS(s) as a major sulfur product (56%–81%), instead of elemental sulfur. The enhancement in the sulfide control performance was much more pronounced when the poorly ordered GFH was used, because of the faster Fe 2+ release, compared to the highly ordered GFO. The abiotic and biotic mechanisms elucidated in this study provide insights into the iron-sulfur chemistry in the sediments of various polluted waters ( e.g., storm drains, urban rivers, and estuary), where the manually-dosed and naturally-occurring Fe III (hydr)oxides control biogenic hydrogen sulfide. Graphical abstract: Image 1 Highlights: FeOOH granules for biogenic sulfide control performed better than those for abiotic sulfide removal. FeOOH granules increased microbial sulfate reduction under organic-rich conditions. The biogenic hydrogen sulfide was mainly converted into amorphous FeS(s) . Microbial iron reduction released substantial Fe 2+ and enhanced sulfide control performance. Poorly ordered FeOOH released more Fe 2+ and performed better in the sulfide control.